Enumeration of probiotic strains from synbiotic samples produced by Myternak Trading - Gnanasekaran, Surenthiran; Noormazlinah, Ahmad; Siti Hajar, Noor Shaarani; Mohd Shafiq, Mohd Sueb; Shariza, Jamek (IOP Publishing, 2020)
Natural defense mechanisms of animals by using probiotics, prebiotics, and synbiotics have been seen as an alternative way to improve animal health and to overcome the food-borne diseases among the livestock. This is as the previous use of antibiotics as the growth promoter in the poultry industry has been banned by the European Union. Synbiotic is a combination of probiotics and prebiotics where probiotics are live microorganisms that give a gainful medical advantage on the host whereas prebiotics are nondigestible food ingredients that influence the host by stimulating the development and the action of a set number of microscopic organisms in the colon. This study was conducted to assess the viability of probiotic strains in the synbiotic powder samples from Myternak Trading as well as to see the correlation between the viability of probiotic strains with the amount of its selective prebiotics. Two different types of prebiotics; fructooligosaccharides (FOS) and inulin with seven different compositions of prebiotics had been used in this study. The viability of probiotic strains in synbiotic powder samples were assessed by enumeration of probiotic strains in two different selective media which are TOS and MRS agar. The highest average colony forming units (CFU) for Bifidobacterium sp. can be found in Batch 7 samples (4.10 × 1011 CFU/ml ) as the volume of FOS is the highest, which is 0.5 mL. While the highest CFU for Lactobacillus sp.can be found in Batch 1 samples (5.560 × 1011 CFU/ml) as the weight of inulin is the highest, which is 5.0 g. These results proved the effects of prebiotic compositions in synbiotics towards the viability of the probiotic strains.. The viable counts of each probiotic strains that contain in the synbiotic powder sample significantly decreases as the amount of selective prebiotic decreases. Therefore, the maximum CFU obtained as the composition of prebiotic increases. Hence it can be concluded that the produced synbiotic powder samples by MyTernak Trading could be used as an alternative feed additive in boosting the livestock health due to the viability of both probiotic strains which are Bifidobacterium sp. and Lactobacillus sp in the synbiotic samples.